Exploring Critical Thinking Skills in Relation to Academic English Proficiency Among University Students - Suranto, Suranto; Pratama, Yoga; Sunarjo, Sunarjo (Journal of Language and Literature Studies, 2026)
In 21st-century higher education, critical thinking has become a pivotal competency in fostering effective language acquisition; however, an empirical gap persists regarding how its specific standard dimensions relate to language outcomes within Indonesian EFL contexts. Therefore, this study aims to analyze the correlation between specific dimensions of critical thinking skills and academic English proficiency. Adopting an explanatory sequential mixed-methods design, this research involved 50 seventh-semester English department students selected via purposive sampling at Universitas Darma Persada. Data were gathered through the standardized California Critical Thinking Skills Test (CCTST)—measuring analysis, evaluation, inference, deduction, and induction—alongside official institutional records of students' standardized English proficiency test scores and student reflection sheets. Quantitative data were analyzed using descriptive statistics and Pearson product-moment correlation, while qualitative data underwent thematic analysis. The quantitative findings revealed that students demonstrated a fair level of critical thinking skills, with a mean score of 26.65 (SD = 3.42). A statistically significant, moderate positive correlation was observed between overall critical thinking skills and academic English proficiency (r = 0.485, p < 0.05). Across specific dimensions, deduction (r = 0.507, p < 0.05) and analysis (r = 0.472, p < 0.05) yielded the strongest significant relationships with language performance. Qualitatively, thematic insights corroborated these results, indicating that critical thinking systematically assisted students in processing complex linguistic frameworks and organizing academic arguments. In conclusion, higher critical thinking proficiency is positively associated with superior academic English proficiency. Pedagogically, these findings imply that higher education institutions should explicitly embed logical deduction and analytical reasoning tasks into curriculum designs to simultaneously cultivate students' linguistic and cognitive competence.